Designing a biostable L-DNAzyme for lead(ii) ion detection in practical samples. Issue 39 (27th September 2016) - Liang, Hao; Xie, Sitao; Cui, Liang; Wu, Cuichen; Zhang, Xiaobing
Abstract : We have constructed a nuclease resistant sensor based on L-DNAzyme for Pd 2+ detection in real water samples and serum solutions. Abstract : A promising biosensor for effective lead(ii ) ion detection in practical applications was developed by constructing a Pb 2+ -specific L-DNAzyme, the enantiomer of the natural nucleic acid-constructed D-DNAzyme. This fluorescence sensor contains the L-enzyme strand with a quencher at the 3′ end, and the L-substrate strand with a fluorophore at the 5′ and a quencher at the 3′ ends that formed a complex. In the presence of Pb 2+, the L-substrate is cut into two fragments, leading to the recovery of fluorescence. The sensor shows high sensitivity and selectivity for Pb 2+ detection with a linear response in the range of 5–100 nM and a detection limit of 3 nM in aqueous solution. Importantly, based on the fact that L-DNAzyme consists of non-natural nucleic acids, which are insensitive to nuclease digestion, protein adsorption and D-DNA hybridization, our sensor shows a specific response to Pb 2+ in practical water and serum samples. Therefore, it is expected that our L-DNAzyme-based strategy may offer a new method for developing simple, rapid and sensitive sensors in complex systems.